PENGEMBANGAN PRODUK DENGAN PENDEKATAN DESIGN THINKING - Layyina, Annisa Kamil; Hussein, Ananda Sabil (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This research was conducted to produce an appropriate product development for Infires Lab, a company engaged in K-Pop merchandise industry. The approach used in this qualitative descriptive research is design thinking, which consists of five stages: empathize, define, ideate, prototype, and test. The informants are collectors of K-Pop merchandise who are also the users of Infires Lab. The data was harvested from semi-structured interviews, observations, and questionnaires. The results of the design thinking analysis indicate that users need special and sturdy products that can protect photocard collections from damage, which are not too small so that they can be found easily, and which are aesthetic in terms of color and design. Based on the results of the usefulness test conducted on users and target users, the produced prototype has fulfilled the need of the users and the K-Pop merchandise collectors.